Enhancing the flexural performance of lightweight concrete slabs with CFRP Sheets: an experimental analysis (Fracture and Structural Integrity, 2024)
The flexural behavior of lightweight concrete two-way slabs is investigated in this work, with a focus on the strengthening or repairing method of externally attaching carbon fiber-reinforced polymer (CFRP) sheets. Five 1000 mm by 1000 mm by 120 mm reinforced lightweight concrete slab slabs were used in the experiment. Tested one specimen with no strengthening and another with CFRP sheet strengthening and repaired the rest with a single layer of CFRP at damage ratios of 50%, 60%, or 70% of the ultimate load, consciously making each slab crack under bending loads while keeping the exact measurements. As to the experiment findings, the ultimate load capacity increased by 30.3% at the strengthened specimen, 17.7% at the 50% damage level, 12.6% at the 60% damage level, and 10.9% at the 70% damage level. As degradation increases, so does the carrying capacity of LWC slabs. The amount of damage LWC slabs sustain influences their stiffness and flexibility. Effectively repairing the sample, CFRP sheets raised the reinforced concrete slabs’ failure stress and stopped the fractures from growing. Reinforced concrete slab failure was increased, and CFRP sheet repairs of the specimens successfully stopped crack propagation.
Keywords: Carbon fiber; CFRP; Damage; Lightweight concrete; Rehabilitation